Ecdysteroids from the Stem Bark of Vitex doniana Sweet (Lamiaceae; ex. Verbenaceae): A Geographically Variable African Medicinal Species - Musa I. Bunu; Derek T. Ndinteh; Jacinta R. Macdonald; Moses K. Langat; Sani M. Isyaka; Nicholas J. Sadgrove; Ingrid Melnikovova; Eloy Fernandez-Cusimamani (MDPI AG, 2021)
Vitex doniana Sweet is an African medicinal species that is prescribed as an aqueous bark extract to be applied topically or orally to achieve anti-infective outcomes. In select regions it is also taken orally as an antimalarial agent. The aim of the current study was to explore the biological properties of V. doniana and isolated compounds in the context of pathogenic bacteria and the protozoan parasite Plasmodium falciparum. Three compounds were isolated and assigned by nuclear magnetic resonance spectroscopy as ecdysteroids: (1) 20-hydroxyecdysone, (2) turkesterone, and (3) ajugasterone C. Interestingly, two of these compounds had not previously been identified in V. doniana, providing evidence of chemical variability between regions. The bark extract and three ecdysteroids were screened for activity against a panel of pathogenic bacteria associated with skin, stomach and urinary tract infections, and the protozoan parasite P. falciparum. The crude extract of the bark inhibited all bacterial strains with MIC values of 125-250 μg.mL−1. The three isolated compounds demonstrated less activity with MIC values of 500-1000 μg.mL−1. Furthermore, no activity was observed against P. falciparum at the screening concentration of 4.8 μg.mL−1. Nevertheless, we present a hypothesis for the possible mechanism for symptomatic relief of malarial fever, which may involve reduction of prostaglandin E(1) & E(2) activity in the hypothalamus via modulation of the monoaminergic system. While further studies are required to identify all antimicrobial agents within this plant species and to determine the cytotoxicity of each of these compounds, these data suggest that the traditional application of this species as an antiseptic is valid.